Mohamed ‘Ali Al-Tajer and His Book ‘Aqd al-La’al fi Tarikh Awal: A Critical reading of its content in the history of Bahrain - Al-Hamadani, Khalid Ismail Nayif (Arab Journal for Sciences and Research Publishing, 2023)
The research sheds light on one of the important local writings that dealt with the history of Bahrain with study, presentation and criticism, as its author, Sheikh Muhammad bin Ali Al-Tajer, is considered one of the pioneers of the historical writing stage that Bahrain witnessed at the beginning of the twentieth century. The History of Bahrain, which presented a comprehensive historical study of Bahrain in his book “‘Aqd al-La’al fi Tarikh Awal”, in addition to that, the study focused on presenting and studying the book’s resources and the various sources on which the author relied, and highlighting the approach adopted by the author in his book, especially with regard to historical narration and literal transmission from some The references are often away from additions or comments, and the research focused, through a critical reading of the book, by highlighting the method of historical writing and methodology adopted by the author, which was characterized by turbulence in the chronology while dealing with the events of the history of Bahrain, as well as his digression and detail on the history of the neighboring countries of Bahrain and other regional countries. This is an extension of the history of Bahrain, and standing on the historical inaccuracies in which the author of the book fell, including the problem of Persia and Bahrain. His reliance on novels and his narration of events that were not mentioned in the original historical sources, and these inaccuracies contributed, which led to historical confusion, distortion and confusion among scholars, and gave an incorrect picture of the history of Bahrain, especially in the historical period that extended since the advent of Islam and its spread in Bahrain and the eras of Islamic history.
Keywords: History of Bahrain; codification; historical fallacies; Mohamed ‘Ali Al-Tajer; Aqd al-La’al